PENGGUNAAN EKSTRAK KAYU SECANG DAN KOL UNGU PADA MEDIA MANITOL SALT AGAR UNTUK MENUMBUHKAN Staphylococcus - Mamay mamay (LPPM Universitas Abdurrab, 2022)
Mannitol Salt Agar (MSA) is a selective and differential medium for isolating Stapylococcus bacteria, distinguishing Staphylococcus aureus bacteria from other species from the ability of mannitol to ferment which changes the color of the phenol red indicator from red to yellow. The use of synthetic indicators that are not environmentally friendly and difficult to decompose can be replaced with natural indicators, including the use of secang wood extract (Caesalpinia sappan L.) and purple cabbage (Brasicca oleraceae). The research was conducted using a descriptive method which describes the color changes of the modified mannitol salt agar (MSA) media of secang wood and purple cabbage extract after being planted with bacteria. Staphylococcus aureus and Coagulation Negative Staphylococcus (CoNS) bacteria were isolated from acne-prone skin. The growth of Staphylococus aureus changed the color of the modified MSA medium from red to yellow for the secang wood extract and the color change from blue to pink for the purple cabbage extract. The growth of CoNS bacteria changed the color of the modified MSA medium from red to red-orange for the secang wood extract and the color change from blue to blue-purple for the purple cabbage extract. Both bacteria thrived on purple cabbage modified MSA media. From this study, it was concluded that secang wood extract and purple cabbage could be used as natural indicators of modified MSA in growing Staphylococcus isolated from the skin.